Short-Term Supplementation of Sauerkraut Induces Favorable Changes in the Gut Microbiota of Active Athletes: A Proof-of-Concept Study - Karačić, Andrija; Zonjić, Jadran; Stefanov, Ena; Radolović, Katja; Starčević, Antonio; Renko, Ira; Krznarić, Željko; Ivančić, Matija; Šatalić, Zvonimir; Liberati Pršo, Ana-Marija (Nutrients, 2024)
Background: Since the gut microbiota is important for athlete health and performance, its optimization is increasingly gaining attention in sports nutrition, for example, with whole fermented foods. Sauerkraut is a traditional fermented food rich in pro-, pre-, and postbiotics, which has not yet been investigated in the field of sports nutrition. Methods: To determine whether sauerkraut could be used for gut microbiota optimization in sports nutrition, a proof-of-concept study was conducted. The microbiota composition of organic pasteurized sauerkraut was analyzed, and then healthy active athletes were provided with the same sauerkraut for 10 days as an intervention. The effects of sauerkraut on the athlete’s gut microbiota, laboratory parameters, and bowel function were assessed. Results: Significant changes in the gut microbiota composition were seen on taxonomic and functional levels, independent of baseline microbiota composition, even after short-term supplementation. Most notably, there was an increase in several health-promoting genera of the family Lachnospiraceae, as well as significant alterations in metabolic pathways regarding cell wall synthesis and the metabolism of nucleotide bases. An increase in the proportion of lymphocytes and a decrease in B12 vitamin levels was observed, as well as a risk of indigestion in certain athletes, which significantly resolved after seven days of supplementation in all athletes. It is unclear whether the observed effects are attributable to the sauerkraut’s own microbiome or its pre- and postbiotics since it is a whole food. Conclusions: Our study has demonstrated that the concept of whole fermented foods, such as sauerkraut, could potentially be feasible and effective in sports nutrition for gut microbiota optimization.